Temporary foreign workers in nursing: Disposable workers? - Jason Foster; Alison Taylor (Adult Education Research Conference, 2011)
This paper explores the experiences of Temporary Foreign Workers in health care in Alberta by examining a cohort of internationally-educated nurses hired to alleviate shortages. In particular it evaluates the assessment of foreign credentials and processes that followed. Drawing on social closure theories, we look at the experiences of foreign workers whose employment and residency status are extremely precarious. We suggest the use of temporary workers to address ‘short term’ labour demand has implications for the workers themselves as well as for larger political, social and economic contexts.